FRI0325 Silent Deposit of MSU Crystals Associates with a More Severe Coronary Calcification in Asymptomatic Hyperuricemic Patients with Acute Coronary Syndrome. (9th June 2015) - Andrés, M.; Quintanilla, M.A.; Sivera, F.; Vela, P.; Ruiz-Nodar, J.M.
Abstract : Background: Increased cardiovascular (CV) risk in gout relates to crystal-driven inflammation. Monosodium urate (MSU) crystals can be found in ∼25% of patients with asymptomatic hyperuricemia (AH) by ultrasound (US). Whether AH patients with crystal deposits show an increased CV risk has not been assessed so far. Objectives: To assess the association between the deposit of MSU crystals in AH and the severity and extension of the coronary atherosclerotic disease (CAD), in comparison with AH patients without crystals and patients with normouricemia (NU). Methods: Cross-sectional study. Consecutive patients admitted due to an acute coronary event were screened. Those with AH (serum uric acid [SUA]≥7.0 mg/dL and no history of gout) were recruited; patients with sustained NU (SUA<7.0mg/dL) were taken as controls. Those with current urate lowering treatment (ULT) were excluded. US of knees and 1st MTP joints was performed to detect signs of MSU crystals deposition in AH patients: doble contour sign, snow storm sign, tophus, or joint effusion. When present, US-guided arthrocentesis was performed to confirm MSU crystals by polarised light microscopy. US and microscopy findings were later reviewed by a blinded rheumatologist. CAD was assessed at coronary angiography by a blinded cardiologist as: a) the presence of moderate-severe coronary calcification; b) the presence of multivessel or left main coronary artery disease; and c) the number of significant coronary stenoses (>50% of the diameter of the vessel). Traditional CV risk factors were also collected. Association between coronariographic features and crystal identification was analysed by non-parametric tests and regression analysis. Results: A total of 140 patients were enrolled, median (p25-75) age 71.5 years (61.0-79.8), 76.4% males. Sixty-six were NU and 74 AH. MSU crystals were identified in 13 of the AH patients (17.5%), so 61 patients were classified as AH without crystals. Clinical characteristics were similar between subgroups, except for a higher prevalence of HTA in both AH subgroups (but not differing between them). AH with crystals patients showed a significantly higher rate of moderate-severe calcification compared to AH without crystals and NU subgroups (84.6%, 36.1%, and 30.3% respectively, p<0, 001) (Figure ). The multivessel disease was more common in both AH subgroups (53.8% crystals; 54.1% no crystals) than in NU (28.8%, p=0.01), but it did not differ between AH subgroups (p=0.55). The median number of significant stenoses were similar between all subgroups (4 in AH with crystals; 3 in AH without crystals; 3 in NU; p=0.09). An adjusted, significant association between the AH with crystals subgroup and the presence of moderate-severe coronary calcification was found (OR 51.67; 95%CI 5.92, 450.80). Conclusions: Silent deposit of MSU crystals independently associated with moderate-severe coronary calcification in AH patients, a marker of a more severe CAD. This finding suggests a deleterious CV effect of MSU crystals in AH. Disclosure of Interest: None declared